2018
DOI: 10.1111/zph.12492
|View full text |Cite
|
Sign up to set email alerts
|

Wild and domestic bird faeces likely source of psittacosis transmission—A case–control study in Sweden, 2014–2016

Abstract: Psittacosis is a zoonotic disease transmitted by birds. In Sweden, where psittacosis is notifiable, an average of eight cases per year were reported between 2002 and 2012. In 2013, an unusual increase in cases in southern Sweden was associated with exposure to wild birds. To further explore specific risk factors connected to wild birds and identify other risk factors for sporadic psittacosis, we conducted a case-control study including all domestically acquired psittacosis cases reported between December 2014 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Studies showed that pregnant women with Chlamydia psittaci infection were prone to miscarriage, malformation and stillbirth, and even increasing the risk of maternal death [8,9] . A case questionnaire in Sweden found that exposed to wild bird or domestic feces or aerosols would predispose to Chlamydia infections [10] . The patient might be at risk of being exposed to Chlamydia psittaci in the environment where he lived.…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that pregnant women with Chlamydia psittaci infection were prone to miscarriage, malformation and stillbirth, and even increasing the risk of maternal death [8,9] . A case questionnaire in Sweden found that exposed to wild bird or domestic feces or aerosols would predispose to Chlamydia infections [10] . The patient might be at risk of being exposed to Chlamydia psittaci in the environment where he lived.…”
Section: Discussionmentioning
confidence: 99%
“…Environmental exposure or direct contact with wild birds other than feral pigeons have been hypothesised sources of infection following case-control studies in Sweden and Australia. In Sweden, two studies identified cleaning wild bird feeders and exposure to bird faecal material to be risk factors for human psittacosis [ 134 , 135 ]. A few years prior to this, bird ringers in Sweden were tested for chlamydial antibodies; however, none showed evidence of seroconversion to C. psittaci , despite a history of directly handling birds [ 136 ].…”
Section: The Role Of Wild Birds In Zoonotic Transmissionmentioning
confidence: 99%
“…While most human cases of psittacosis with a confirmed association with wild birds have involved close contact with and handling of wild birds (e.g., wild birds brought into vet surgeries [ 109 ]), as discussed above, some cases have been linked to cleaning wild bird feeders [ 135 ] and mowing lawns without a grass catcher [ 9 ]. This highlights the potential benefits of greater public awareness and perhaps proactive human or wild bird surveillance in communities suspected at risk (such as the proactive surveillance described in [ 8 ]).…”
Section: The Role Of Wild Birds In Zoonotic Transmissionmentioning
confidence: 99%
“…From January to April 2013, 25 individuals from southern Sweden were diagnosed with psittacosis [54]. Wild birds were thought to be the source of infection in both outbreaks [53,55]. C. psittaci Ful127 is thought to be the responsible agent for a psittacosis outbreak with 174 human cases on the Faroe Islands in the 1930s [33].…”
Section: Public Health Concernsmentioning
confidence: 99%